Association of Child Pugh Class with Esophageal Varices and Portal Hypertensive Gastropathy in Patients with Cirrhosis: Child-Pugh Classification and Portal Hypertension in Cirrhosis - Hussain, Sayed Imtiaz; Seerani, Nand Lal; Qureshi, Aleem Riaz; Soomro, Ubedullah; Samejo, Khadim Hussain; Baig, Muhammad Sohail (Pakistan Journal of Health Sciences, 2025)
Oesophageal-varices and portal-hypertensive-gastropathy are common in cirrhotic-patients. The Child Pugh-classification, a key measure of liver disease severity, helps assess their association, offering insights into disease progression and management. Objective: To determine the association between Childs PUGH class, oesophageal varices and portal hypertensive gastropathy in patients with cirrhosis. Methods: This Cross Sectional Study was conducted at the Department of Gastroenterology, LUMHS, Jamshoro, Pakistan. Doppler ultrasound was used to diagnose portal hypertension. Following the ultrasound, endoscopy was performed to diagnose oesophageal varices and portal hypertensive gastropathy. The data collected were electronically recorded for research purposes using the provided proforma. Results: Oesophageal varices were noted in 122 (88.4%) patients and portal hypertensive gastropathy in 117 (84.8%) patients. In association of Child-Pugh class with oesophageal varices, class A was noted in 9.4%, class B in 23.2%, and class C in 55.8% of patients resulting in a significant p- value of 0.008 whereas in the association of Child-Pugh-class with portal-hypertensive-gastropathy, class A was noted in 8.0%, class B in 23.9%, while class C had 52.9% resulting in a non-significant p- value of 0.122. Conclusions: This study found a strong association between cirrhosis severity and the presence of esophageal varices, with the highest prevalence observed in Child-Pugh Class C patients (p = 0.008). However, the association between Child-Pugh class and portal hypertensive gastropathy was not statistically significant (p = 0.122).